The Practicality of Teaching Materials Supplements for Growth and Development Materials Based on Drought-stressed Plants - Rahwilin Van Gobel; Frida Maryati Yusuf; Novri Youla Kandowangko (Postgraduate, University of Mataram, 2023)
The purpose of this study is to decrypt the practicality of teaching material supplements for growth and development materials based on drought-stricken plant studies. This research includes development research using the ADDIE development model which consists of five stages, namely Analysis, Design, Development, Implementation, and Evaluation, with the test subjects involving 20 students from class XII science of SMA Negeri 4 Gorontalo in 2022/2023. Practicality is a stage of development research. The instrument used in the practicality of teaching material supplements is measured by the implementation of learning, student activities, and student responses. The results showed that the implementation of learning reached 100%, at meeting 1 and meeting II it reached 100 % with excellent categories, student activity with 76.87% good categories, and student responses with 88.07% with excellent categories. Thus, the supplement of teaching materials for growth and development materials based on the study of drought-stricken plants is practically used in the biology learning process on growth and development material